Naja atra Cardiotoxin 3 Elicits Autophagy and Apoptosis in U937 Human Leukemia Cells through the Ca(2+)/PP2A/AMPK Axis - Chiou, Jing-Ting (Toxins (Basel), 2019)
Cardiotoxins (CTXs) are suggested to exert their cytotoxicity through cell membrane damage. Other studies show that penetration of CTXs into cells elicits mitochondrial fragmentation or lysosome disruption, leading to cell death. Considering the role of AMPK-activated protein kinase (AMPK) in mitochondrial biogenesis and lysosomal biogenesis, we aimed to investigate whether the AMPK-mediated pathway modulated Naja atra (Taiwan cobra) CTX3 cytotoxicity in U937 human leukemia cells. Our results showed that CTX3 induced autophagy and apoptosis in U937 cells, whereas autophagic inhibitors suppressed CTX3-induced apoptosis. CTX3 treatment elicited Ca(2+)-dependent degradation of the protein phosphatase 2A (PP2A) catalytic subunit (PP2Acα) and phosphorylation of AMPKα. Overexpression of PP2Acα mitigated the CTX3-induced AMPKα phosphorylation. CTX3-induced autophagy was via AMPK-mediated suppression of the Akt/mTOR pathway. Removal of Ca(2+) or suppression of AMPKα phosphorylation inhibited the CTX3-induced cell death. CTX3 was unable to induce autophagy and apoptosis in U937 cells expressing constitutively active Akt. Met-modified CTX3 retained its membrane-perturbing activity, however, it did not induce AMPK activation and death of U937 cells. These results conclusively indicate that CTX3 induces autophagy and apoptosis in U937 cells via the Ca(2+)/PP2A/AMPK axis, and suggest that the membrane-perturbing activity of CTX3 is not crucial for the cell death signaling pathway induction.